Penentuan Bahaya Longsor Berdasarkan Pedoman Penilaian Tingkat Risiko Lereng Jalan (Ruas Waipia-Saleman) - Pebrinar Riani Sangle; Irwan Lie Keng Wong; Lisa Febriani (Indonesian Society of Applied Science, 2026)
Landslides are one of the most frequent geological disasters in Indonesia, leading to significant losses to infrastructure and the economy, especially in areas with particularly steep topography, such as Seram Island, Central Maluku. The island is susceptible to landslides due to a combination of natural factors such as high, heavy rainfall, mountainous topography, and seismic activity, as well as anthropogenic factors such as deforestation and agricultural activities on slopes. The objective of this study is to evaluate the landslide hazard in Seram Island (Waipia-Saleman Section) by identifying high-risk areas using the 2018 road slope assessment guidelines. From the analysis result along the Waipia-Saleman section, it was found that there were 6 points with very high potential for landslide, 1 point with a high potential for landslide, 4 points with medium potential for landslide, and 2 points with low potential for landslide. Mitigation recommendations at 6 spots with very high potential slopes were made to reconstruct the slopes. Instrument installation and rehabilitation were conducted at 1 spot with a high potential slope. At the 4 spots with medium potential slopes, rehabilitation was recommended as the mitigation, while the 2 spots with low potential slopes were assigned periodic maintenance.